2016
DOI: 10.1186/s13046-016-0357-4
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-361-3p suppresses tumor cell proliferation and metastasis by directly targeting SH2B1 in NSCLC

Abstract: BackgroundLung cancer is the most common malignancies worldwide. However, the detailed molecular mechanisms underlying lung cancer progression are still not completely clear. MicroRNAs are small noncoding RNAs which occupy a crucial role of cancer metastasis. Accumulating evidence suggests that miR-361 plays important roles in human carcinogenesis. However, its precise biological role remains largely elusive, especially in lung cancer. This study examined the role of miR-361-3p in non-small cell lung cancer (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 43 publications
4
66
0
Order By: Relevance
“…It has been demonstrated that SH2B1 acts as an oncogene in lung cancer, esophageal cancer and neuroblastoma (9)(10)(11)(12). However, its functions in GC remain unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that SH2B1 acts as an oncogene in lung cancer, esophageal cancer and neuroblastoma (9)(10)(11)(12). However, its functions in GC remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…All three members share a common domain structure that includes a dimerization domain, a pleckstrin homology domain, several proline-rich regions and a SH2 domain near the C-terminus (7). Previous studies have demonstrated that SH2B1 contributes to the malignant progression of tumors, including colon, ovary and non-small cell lung tumors (8)(9)(10)(11)(12). However, the effect of SH2B1 expression on GC has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small non‐coding RNAs that function by binding to the 3′‐untranslated regions (UTRs) of target mRNAs. Recent studies have demonstrated the involvement of miRNAs, such as miR‐29, miR‐143, miR‐191, and miR‐361, in regulating EMT, and tumor metastasis in NSCLC . Many miRNAs are dysregulated in cancer metastasis, and there are likely additional miRNAs involved in this process, which have not yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the involvement of miRNAs, such as miR-29, miR-143, miR-191, and miR-361, in regulating EMT, and tumor metastasis in NSCLC. [17][18][19][20] Many miRNAs are dysregulated in cancer metastasis, and there are likely additional miRNAs involved in this process, which have not yet been identified. We previously demonstrated that miR-3127-5p, which functions as a tumor suppressor, is downregulated in NSCLC, and associated with clinical stage and tumor recurrence.…”
mentioning
confidence: 99%
“…9 Both in central nervous system and in peripheral tissues, SH2B1 is widely expressed and systemic changes in SH2B1 expression, dominantly deletion mutation, could have profound effects to result in energy imbalance, obesity, severe leptin resistance, and type 2 diabetes in mice and humans. 17 Clinical importance for the field of SH2B1 research is not only focused on endocrine disease, 18,19 but also concerned with some solid tumors, including lung cancer, 20,21 esophageal cancer, 22 and thyroid carcinomas, 23 which detected somatic gain-of-function mutations. In addition, emerging several lines of basic research in cultured cells show that the function of SH2B1 is involved in actin cytoskeletal reorganization, 24,25 focal adhesion assembly and disassembly, 26 filopodium formation, 27,28 and mitogenic response, 29 suggesting that SH2B1 could regulate cells motility, 24,30 proliferation and differentiation 17,29 by enhancing Rac, 30 RET, 23 mTOR, 31 and STATs 29 signals, which are generally established mediators in tumorigenesis and EMT program in tumors.…”
Section: Introductionmentioning
confidence: 99%